SUFIKS BAHASA INGGRIS DAN BAHASA TONTEMBOAN (SUATU ANALISIS KONTRASTIF) - Tenda, Tirza Kartika (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This research is entitled â€œSuffixes in English and Tontemboan language (A Contrastive Analysis)â€. The objectives of this research are to identify, classify and describe the suffixes and to analyze the similarities and differences of suffixes used in both languages. This research uses a descriptive method. There are three steps to finish this research, the first step is preparation. In this step, the writer reads some books about suffixes. The second step is data collection. In this step, the writer collect the kind of suffixes that include in suffixes in English and Tontemboan language. The third step is data analysis. In this step, the writer identifies, classifies, and describes the data about suffixes in English and Tontemboan language according to Oâ€™Grady and Dobrovolskyâ€™s (1992) theory and then the writer uses Lado (1957) and Whitman (1970) theory to find out the similarities and the differences of the structures in this case the suffixes of both languages in terms of forms, functions and meanings. The result shows that English and Tontemboan language have suffixes. The functions of English Suffixes are to form nouns, verbs, adjectives, and adverbs. While the function of Tontemboan suffixes are nouns, verbs, and adjectives. Keywords: Suffixes, English and Tontemboan language, Contrastive analysis.